3r+11=2-3(3r+3)

Simple and best practice solution for 3r+11=2-3(3r+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3r+11=2-3(3r+3) equation:


Simplifying
3r + 11 = 2 + -3(3r + 3)

Reorder the terms:
11 + 3r = 2 + -3(3r + 3)

Reorder the terms:
11 + 3r = 2 + -3(3 + 3r)
11 + 3r = 2 + (3 * -3 + 3r * -3)
11 + 3r = 2 + (-9 + -9r)

Combine like terms: 2 + -9 = -7
11 + 3r = -7 + -9r

Solving
11 + 3r = -7 + -9r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '9r' to each side of the equation.
11 + 3r + 9r = -7 + -9r + 9r

Combine like terms: 3r + 9r = 12r
11 + 12r = -7 + -9r + 9r

Combine like terms: -9r + 9r = 0
11 + 12r = -7 + 0
11 + 12r = -7

Add '-11' to each side of the equation.
11 + -11 + 12r = -7 + -11

Combine like terms: 11 + -11 = 0
0 + 12r = -7 + -11
12r = -7 + -11

Combine like terms: -7 + -11 = -18
12r = -18

Divide each side by '12'.
r = -1.5

Simplifying
r = -1.5

See similar equations:

| -7+x=-3x+25 | | 3ln(5x+4)=22 | | 4(4x-9)-6=4(x-4)+46 | | 16x^2-7t=17t-9 | | 36-6x=14+5x | | 2u^2+13u+15=0 | | (4x^2)+4x+(4y^2)-32y-335=0 | | 4x^2-147=0 | | (7/2)^-1=-1/7x | | (X-7)/2=(5-x)/4 | | 54-8x=18+10X | | 3(3x+5)=60 | | 8(3t-5)+12=-8 | | 54-8x=18+10 | | 16x^3-132x+252=0 | | 2+3(x+1)=9-3+2x | | 4(x+7)=-2x+34 | | x^3+8x^2+20x=0 | | 8x^2+5x+25=0 | | 5x+2=14+6X | | 13(17-x)=15(x+1) | | -7(1-2x)+8=-83 | | g(x)=3(5)x | | 4r^2-r+3=0 | | 3v+6=9-3(2v-2) | | x+3(x+6)=4(2x+1) | | 4(3z-3)=18 | | (2x-17)/5=-5 | | -11=3(v-7)-8v | | 13+x+2x=6x+1 | | 4x^2+8x+36=0 | | 73/100=81 |

Equations solver categories